Chrysanthemum at a glance - Prasad, K V; Saha, Tarak Nath (Indian Horticulture, 2019)
Popularly known as the Queen of the East and became the national flower of Japan. Commercially grown for loose flowers, cut flowers production and as potted plant (pot mums). Third most important commercial loose flower crop after Rose and Marigold in India. Chrysanthemum is a typical short day plant that flowers in winters. However, year round production is possible by growing photo and thermo insensitive varieties and regulating the light cycles.